La conversion de saint Augustin : modèle paradigmatique ou exemple atypique ? - Béatrice Bakhouche (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Augustine’s Confessions, and its central scene in the garden at Milan, have always been opened to many different interpretations. This article first deals with the structure of the work as a conversion narrative and then examines the dramatic structure of the famous garden scene, especially the way it answers and opposes other passages in the text. This will enable us to define, still in the light of the Confessions, the way this climactic episode marks changes and continuities in Augustine’s life.